Pengaruh Persediaan Bahan Baku Dan Kapasitas Mesin Terhadap Volume Produksi (Studi Kasus Pada UMKM Raflesia Bordir Mukena Di Tasikmalaya) - Ima Herdiana; Suci Putri Lestari; Barin Barlian (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This purpose of this study to determine the influence of raw material inventory and machine capacity on production volume (Case study on UMKM Raflesia Bordir Mukena at Tasikmalaya). The method used is a quantitative method with a research sample data on raw material inventory, machine capacity and production volume for the period 2019 – 2021. The data is used primary data and secondary data. The analitytical tool in this research is multiple regression using by SPSS version 25. The result showed that simultaneously raw material inventory and machine capacity has a significant influence on production volume. Partially raw material inventory has unsignificant on production volume. Machine capacity has significant on production volume.